Evaluation of insecticides for control of the spotted lanternfly, Lycorma delicatula, (Hemiptera: Fulgoridae), a new pest of fruit in the Northeastern U.S. (October 2019) - Leach, Heather; Biddinger, David J.; Krawczyk, Greg; Smyers, Erica; Urban, Julie M.
Abstract: The spotted lanternfly, Lycorma delicatula (White) (Hemiptera: Fulgoridae), was first detected in the United States in southeastern Pennsylvania in late 2014. Since then, the range of this polyphagous pest has increased to multiple states in the Northeastern U.S., threatening many agricultural commodities, including grape and tree fruit. Several insecticides were tested for residual efficacy on eggs, nymphs, and adult L. delicatula . In both laboratory and field bioassays on L. delicatula egg masses, chlorpyrifos was the only compound to provide 100% mortality and paraffinic oil offered intermediate mortality up to 71%. In semi-field and field bioassays against L. delicatula nymphs and adults, several compounds from multiple insecticide classes, including pyrethroids, neonicotinoids, carbamates, and organophosphates, had excellent knockdown activity. However, only thiamethoxam and bifenthrin offered control of 50% or greater up to 14 days after the application for adults. None of the OMRI-listed compounds evaluated in this study provided effective control, indicating anticipated difficulty among organic producers in reducing damage from this new and important pest. As L. delicatula continues to expand its geographic range, we may have to be reliant on chemical control until biological or other cultural control measures are discovered and implemented. These data have helped to formulate pest management programs as a first response to this invasive insect. Highlights: Spotted lanternfly ( Lycorma delicatula ) is a new and destructive invasive insect. Field and semi-field insecticide efficacy assays were conducted for L. delicatula . Chlorpyrifos was found to be effective at killing 100% of eggs. Thiamethoxam and bifenthrin offered control of adults up to 14 days.